Neither housing nor hotel: The emergence of “medium-term rentals” in post-Covid Canadian cities - Wachsmuth, David; Buglioni, Bridget (Canadian Planning and Policy / Aménagement et politique au Canada)

(untitled) (Association of Canadian University Planning Programs, 2024)
One of the many impacts of the Covid pandemic on Canadian cities was the complete collapse of short-term rental (STR) markets, as long-distance travel nearly vanished for more than a year. Many dedicated STRs shifted back to the long-term rental market, but others remained on STR platforms such as Airbnb but with minimum stays of one month or more—a land use we describe as “medium-term rentals” (MTRs). This paper provides a planning analysis of online-platform-mediated MTRs in Canadian cities and their housing-market, land-use, and regulatory implications. First, we identify and explore the regulatory grey zone inhabited by MTRs, which appear to be neither standard residential tenancies nor short-term tourist accommodations. Second, the paper provides a brief empirical overview of the emergence of MTRs during and after the Covid pandemic in Toronto, Montreal, and Vancouver. Third, the paper uses a policy case study of situations in which Ontario’s Landlord and Tenant Board has been asked to adjudicate non-standard tenancies to establish whether there is a planning basis for distinguishing medium-term rentals from other tenancy types. The paper concludes by identifying a key planning principle which could allow Canadian municipalities to pull MTRs out of the regulatory grey zone: regulating type of stay instead of length of stay.